Optimizing a 2D active set-up for global control of low-frequency wall reflections in a semi-anechoic room - Friot Emmanuel; Pinhède Cédric; Herzog Philippe; Boulandet Romain (Acta Acustica)
Numerical simulations were carried out to optimize the design of an active semi-anechoic room. The active set-up includes control sources and microphones near the room ceiling and walls. The objective is to achieve global control, around an a priori unknown primary source, of the low-frequency wall reflections that are not adequately managed by absorbing material. The control strategy is based on the estimation, by linear filtering of total pressure signals, of the scattered pressure at minimization points meshing the room ceiling and walls. The required filters are identified off-line from measurements with a source whose radiation pattern is known. A 2D simple modal model is used to simulate active control in the frequency domain. The location of the minimization points, the set of estimation microphones and the method for computing the control signals from the measurements are varied. Simulations show that i) efficient global control of the scattered pressure can be achieved over a wide frequency band with a single non-smooth layer of minimization points, ii) accurate scattered pressure estimation at the minimization points can be achieved using usual pressure microphones distributed over all walls, iii) a Remote-Microphone technique seems slightly preferable to an Additional-Filter method for calculating the control signals.